Investigation of perfluorinated proton exchange membranes prepared via a facile strategy of chemically combining poly(vinylphosphonic acid) with PVDF by means of poly(glycidyl methacrylate) grafts - Sinirlioglu, Deniz; Muftuoglu, Ali Ekrem; Bozkurt, Ayhan (SPRINGER, 2015)
A versatile and diverse grafting method was employed in the preparation of perfluorinated PEMs, in which poly(vinyl phosphonic acid) (PVPA) and poly(vinylidene fluoride) (PVDF) were chemically combined by means of poly(glycidyl methacrylate) (PGMA) grafts. Alkaline treated PVDF was used as a macromolecule in conjunction with GMA in the graft copolymerization. Various PVDF-g-PGMA-g-PVPA membranes were obtained upon simply mixing PVDF-g-PGMA and PVPA at several ratios by mass. The composition and the structure of the membranes were characterized by Energy Dispersive X-ray spectroscopy (EDS), H-1-NMR, F-19-NMR, and FTIR. Thermogravimetric analysis (TGA) demonstrated that the PVDF-g-PGMA and PVDF-g-PGMA-g-PVPA membranes were thermally stable up to 275 and 210 degrees C, respectively. The surface roughness and morphology of the membranes were studied using Atomic Force Microscopy (AFM), X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). The proton conductivity increased with increasing temperature and PVPA ratio in the absence of humidity. The maximum proton conductivity in anhydrous conditions at 150 degrees C was 0.0023 Scm(-1) while in humidified conditions (under 50 % of RH) at 100 degrees C a value of 0.034 Scm(-1) was found.
Keywords: PVDF; Fuel cells; Poly(vinylphosphonic acid); Alkaline treatment; Proton conductivity; TRANSFER RADICAL POLYMERIZATION; POLY VINYLPHOSPHONIC ACID; POLY(VINYLIDENE FLUORIDE); ELECTROLYTE MEMBRANES; CONDUCTING MEMBRANES; FUEL-CELL; COPOLYMER ELECTROLYTES; GLYCIDYL METHACRYLATE; HIGH-TEMPERATURE; SURFACE MODIFICATION; Polymer Science